2015
DOI: 10.1371/journal.pone.0133934
|View full text |Cite
|
Sign up to set email alerts
|

Combined Usefulness of the Platelet-to-Lymphocyte Ratio and the Neutrophil-to-Lymphocyte Ratio in Predicting the Long-Term Adverse Events in Patients Who Have Undergone Percutaneous Coronary Intervention with a Drug-Eluting Stent

Abstract: ObjectivesThe aim of this study was to investigate the combined usefulness of platelet-to-lymphocyte ratio (PLR) and neutrophil-to-lymphocyte ratio (NLR) in predicting the long-term adverse events in patients who have undergone percutaneous coronary intervention (PCI) with a drug-eluting stent (DES).Methods798 patients with stable angina, unstable angina and non-ST elevated myocardial infarction (NSTEMI) who underwent elective successful PCI with DES were consecutively enrolled. The value of PLR and NLR in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
58
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 33 publications
7
58
2
2
Order By: Relevance
“…Thus far, many authors reported a high admission PLR to be a significant predictor short-and long-term mortality in patients with acute coronary syndromes (Cho, Ann, Singh, Her, & Shin, 2015;Cicek et al, 2015;Hudzik et al, 2015;Ozcan Cetin et al, 2016;Toprak et al, 2015). Ozcan Cetin et al examined PLR prognostic value on in-hospital and long-term MACE (stent thrombosis, nonfatal myocardial infarction, and mortality) in patients with STEMI.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, many authors reported a high admission PLR to be a significant predictor short-and long-term mortality in patients with acute coronary syndromes (Cho, Ann, Singh, Her, & Shin, 2015;Cicek et al, 2015;Hudzik et al, 2015;Ozcan Cetin et al, 2016;Toprak et al, 2015). Ozcan Cetin et al examined PLR prognostic value on in-hospital and long-term MACE (stent thrombosis, nonfatal myocardial infarction, and mortality) in patients with STEMI.…”
Section: Discussionmentioning
confidence: 99%
“…For descriptive statistics, continuous variables were presented as mean ± standard deviation (SD), and nominal variables were presented as the number of patients (n) and percentage [5]. In univariate analysis and cross-tables, chisquare and Fisher's exact chi-square tests were used.…”
Section: Discussionmentioning
confidence: 99%
“…Because the normal range for RDW is considered to be 11.5-15.6, the cutoff value was set as >15.6. The high threshold for MPV was set as 8.75 [4], and the cutoff values for PLR and NLR were set as 128 [5] and 2.81 [6], respectively.…”
Section: Patients and Data Acquisitionmentioning
confidence: 99%
“…The neutrophil-to-lymphocyte ratio (NLR) and the platelet-tolymphocyte ratio (PLR) parameters have been reported to be cost-effective measures of many systemic inflammatory processes [3,4,13,14]. Moreover, Lappé et al [15] demonstrated that the red cell distribution width (RDW), which measures the variation in red blood cell size, is associated with chronic inflammation.…”
mentioning
confidence: 99%